Asymptotically optimal quantum channel reversal for qudit ensembles and multimode Gaussian states - Bowles, P.; Guţă, M.; Adesso, Gerardo (IOP Publishing, 2012)
We investigate the problem of optimally reversing the action of an arbitrary quantum channel C which acts independently on each component of an ensemble of n identically prepared d-dimensional quantum systems. In the limit of large ensembles, we construct the optimal reversing channel R☆n which has to be applied at the output ensemble state, to retrieve a smaller ensemble of m systems prepared in the input state, with the highest possible rate m/n. The solution is found by mapping the problem into the optimal reversal of Gaussian channels on multimode quantum-classical continuous variable systems, which is solved here as well. Our general results can be readily applied to improve the implementation of robust long-distance quantum communication. As an example, we investigate the optimal reversal rate of phase flip channels acting on a multi-qubit register.